Web-based Application Design "UMB Eats" With Laravel Framework - Afiyati, Afiyati; Fahrezi, Zidane; Rizky, Muhammad; Ardi, Liandy Hayanto; Ahmad, Ersa (Journal Collabits, 2025)
The ‘UMB Eats’ application was developed to improve the efficiency of Mercu Buana University canteen services by providing online ordering and payment features. This application makes it easier for users to access menu information, prices, and food stocks, while reducing long queues at the canteen. This research aims to design a web-based system that is practical and helps the management of orders and stock by sellers. As a result, ‘UMB Eats’ proved to provide a faster and more convenient experience for users, as well as supporting a more organised canteen operation.